Etherified pullulan-polyethylenimine based nanoscaffolds improved chemosensitivity of erlotinib on hypoxic cancer cells. (1st November 2021) - Bera, Hriday; Abosheasha, Mohammed A.; Ito, Yoshihiro; Ueda, Motoki
Abstract: The current research endeavor aimed to accomplish hypoxia-responsive polyethyleneimine-conjugated carboxymethyl pullulan-based co -polymer (CMP-HA-NI-PEI-NBA) bearing nitroaromatic subunits to efficiently deliver erlotinib (ERL) to reverse its hypoxia-induced resistance in cancer cells. As compared to a control co-polymer (CMP-HA-MI-PEI-BA) devoid of hypoxia-sensitive moieties, this scaffold demonstrated a hypochromic shift in the UV spectra and rapid dismantling of its self-assembled architecture upon exposure to simulated hypoxic condition. The hypoxia-responsive co -polymer encapsulated ERL with desirable loading capacity (DEE, 63.05 ± 2.59%), causing attenuated drug crystallinity. The drug release rate of the scaffold under reducing condition was faster relative to that of non-reducing environment. Their cellular uptake occurred through an energy-dependent endocytic process, which could exploit its caveolae/lipid raft-mediated internalization pathway. The ERL-loaded scaffolds more efficiently induced apoptosis and suppressed the proliferation of drug-resistant hypoxic HeLa cells than the pristine ERL. Hence, this study presented a promising drug delivery nanoplatform to overcome hypoxia-evoked ERL resistance. Graphical abstract: Unlabelled Image Highlights: Carboxymethyl pullulan/polyethyleneimine basedco-polymer was synthesized. The selective-hypoxic bioreduction of the co-polymer was evidenced. ERL-loaded nanoscaffolds displayed hypoxia-triggered drug release pattern. These exploited caveolae/lipid raft-mediated internalization pathway. These showed an efficient antiproliferative potential on the hypoxic cancer cells.